Democracy in Central Eastern Europe and European Union - Muskaj, Blerina (European Journal of Multidisciplinary Studies, 2022)
Some of the countries in the region have contributed through assistance programs to develop and align their democracies with what the EU itself lobbies. EU aid to CEE is seen as a phenomenon of EU-perceived responsibility in the interaction of new democracies in Central and Eastern Europe. This paper will create a genuine study of the perceived responsibility for the development of democracies in these countries. It paints a clear picture of the development of democracy and the need for CEE countries to be under EU assistance. The assistance coming from this institution has given and continues to contribute to developing a democracy with strong executive foundations for society and beneficial to the region. In this way, the EU manages to achieve its objectives of achieving a federal union. When we say federal union we mean a Europe with the same democratic values and executive standards.In this paper the EU's responsibility for the new democracies of Central and Eastern Europe is seen in activities with EU programs to enhance institutions above democratic values. Having access to the issues facing the democracies of Central and Eastern Europe, the Council Acquis provides an overview in the field of democracy. The paper gives us the opportunity to look more closely at democratic forces in countries where the latter is still developing, aiming not only at the analysis of democracy, but also at the analysis of the European common market. We will look at these two EU phenomena in the context of the EU's perceived responsibility for the interaction of new democracies in CEE. The EU has undertaken this responsibility in the context of strengthening, developing and maturing new democracies on the European Continent. Giving its contribution through various programs designed in the form of grants, which are given to countries that are in the process of maturation, in the form of programs that pave the way for development. The question that arises at this stage is: Does democracy help in a market economy?
Keywords: market economy, Acquis, council, democracies, Central-Eastern Europe